X 4 3x 2 12x
![x 4 3x 2 12x](https://content.bartleby.com/qna-images/question/5fa544c9-c440-4f94-850d-73173a8a80d4/e7e520db-51bb-4748-b635-0c0f9b532d14/7sthwa6.jpeg)
- Simplify x 4 3x 2 12x
- X 4 3x 3 4x 2 12x
- X 4 3x 3 8x 2 12x 16 0
- X 4 3x 3 8x 2 12x 16
- X 4 6x 3 3x 2 12x 10
- X 4 3x 3 4x 2 12x 0
- X 4 3x 3 2x 2 12x 8
- X 3x 4 )- 3 x 2 2 )+ 12x
- X 3 3x 2 12x 4 0
- Q x )=- 4x 5 2x 4 3x 2 12x
- 3x 2 12x x 4 0
- F x )= 3x 2 12x 4
- F x )= x 4 3x 3 4x 2 12x
- F x )= 3x 4 4x 3 12x 2 12
- F x )= 3x 4 4x 3 12x 2 5